Immune gene expression in the mosquito vector Culex quinquefasciatus during an avian malaria infection. Issue 4 (14th December 2022) - García‐Longoria, Luz; Ahrén, Dag; Berthomieu, Arnaud; Kalbskopf, Victor; Rivero, Ana; Hellgren, Olof
Abstract: Plasmodium relictum is the most widespread avian malaria parasite in the world. It is listed as one of the 100 most dangerous invasive species, having been responsible for the extinction of several endemic bird species, and the near‐demise of several others. Here we present the first transcriptomic study focused on the effect of P. relictum on the immune system of its vector (the mosquito Culex quinquefasciatus ) at different times post‐infection. We show that over 50% of immune genes identified as being part of the Toll pathway and 30%–40% of the immune genes identified within the Imd pathway are overexpressed during the critical period spanning the parasite's oocyst and sporozoite formation (8–12 days), revealing the crucial role played by both these pathways in this natural mosquito– Plasmodium combination. Comparison of infected mosquitoes with their uninfected counterparts also revealed some unexpected immune RNA expression patterns earlier and later in the infection: significant differences in expression of several immune effectors were observed as early as 30 min after ingestion of the infected blood meal. In addition, in the later stages of the infection (towards the end of the mosquito lifespan), we observed an unexpected increase in immune investment in uninfected, but not in infected, mosquitoes. In conclusion, our work extends the comparative transcriptomic analyses of malaria‐infected mosquitoes beyond human and rodent parasites and provides insights into the degree of conservation of immune pathways and into the selective pressures exerted by Plasmodium parasites on their vectors.